Atrioventricular conduction disturbance during pulmonary vein isolation using the second-generation cryoballoon — Vagal impact of cryoballoon ablation. (15th August 2018) - Miyazaki, Shinsuke; Kajiyama, Takatsugu; Watanabe, Tomonori; Hada, Masahiro; Yamao, Kazuya; Nakamura, Hiroaki; Hachiya, Hitoshi; Tada, Hiroshi; Hirao, Kenzo; Iesaka, Yoshito
Abstract: Background: Vagal reactions of the sinus node during pulmonary vein isolation (PVI) have been reported, however, data on intra-procedural atrioventricular conduction disturbances have been sparse. The present study aimed to investigate the clinical characteristics of atrioventricular conduction block (AVB) during PVI using second-generation cryoballoons. Methods: A total of 2252 PVs among 568 consecutive atrial fibrillation patients undergoing PVI with 28-mm cryoballoons were analyzed. In 44 patients, left superior PVs (LSPVs) were initially targeted (initial-LSPV-group). In the remaining 524 patients, LSPVs were targeted following right superior PVs (RSPVs) (initial-RSPV-group). Results: Marked sinus arrests/bradycardia occurred in 14 patients only in the initial-LSPV-group, and the incidence was significantly higher in the initial-LSPV than initial-RSPV-group (14/44 vs. 0/524, p < 0.001). Intra-procedural AVB with 3.6 [1.9–8.2] second maximal RR intervals appeared in 12 patients during freezing (n = 1) or after balloon deflation following freezing (n = 11). The targeted PVs were the LSPV, left common PV, right inferior PV, and RSPV in 8, 1, 2, and 1 patients, respectively. The incidence was similar between the initial-LSPV and initial-RSPV-groups (1/44 vs. 11/524, p = 0.938). Four patients exhibited complete AVB with more than a 6 s maximal RR interval. Three patients experienced AVB during atrial fibrillation. AVB was observed a median of 23.0 [15.0–70.0] seconds after balloon deflation and 76.0 [60.0–125.0] seconds after freezing termination. AVB persisted for 56.0 [36.0–110.0] seconds, and all recovered spontaneously with or without requiring back-up pacing. Conclusions: A marked transient AV conduction disturbance could occur after balloon deflation, especially during LSPV ablation, regardless of the order of targeted PVs.